Васинський курган середньоскіфського часу - Козир, І.А.; Панченко, К.І.; Чорний, О.В. (Археологія і давня історія України, 2019)
У статті подаються результати дослідження кургану середньоскіфського часу біля с. Васине
Знам'янського р-ну Кіровоградської обл. Пам'ятка
вирізняється особливим типом наземної дерев'яної
поховальної споруди, яка добре збереглася. В науковий обіг вводиться нова знахідка кам'яної антропоморфної стели. The article presents the results of a study from the
excavation of the barrow of middle Scythian time in
Vasyne (Znamensky district, Kirovograd region). Barrow
was located in the upper reaches of the river Beshka,
the right tributary of the Ingulets in its upstream. The main Scythian burial was committed on the surface
of the ancient horizon. A complex wooden burial structure constructed of oak was partially burnt, but well
preserved. In the center of the entire burial facility was a ground-based square ten-column wooden tomb (5.5 ×
5.5 m) with a flat ceiling, around which a «pyramid» was built of horizontal layers of raw tree trunks, logs
and logs, preserved to a height of 0.9—1,4 m. «Pyramid » at the level of the ancient horizon was surrounded
by thin (5—7 cm) wooden flooring. The overall diameter of the wooden structure reached 19 m.